EXPLORATION OF CHALLENGES AND OPPORTUNITIES IN THE INTEGRATION OF PRODUCT INNOVATION AND DIGITAL MARKETING IN THE DEVELOPMENT OF MSMEs IN THE FOOD SECTOR - Muh. Husriadi; Fari Aus; Siti Kadri Yanti Sari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economies of developing countries, but face significant challenges in integrating product innovation and digital marketing. This study reveals that limited resources, both financial and human resources, as well as low digital literacy, are the main obstacles in optimizing MSME digital marketing strategies. Many business actors have difficulty using advanced digital marketing technology and analytical tools, resulting in ineffective marketing strategies. However, this study also found great opportunities through the use of customer data for product innovation and market expansion via digital platforms. By utilizing social media and e-commerce, MSMEs can expand their markets and reduce operational costs. These findings indicate that developing digital literacy and collaborating with the government and e-commerce platforms are essential to support the growth and sustainability of MSMEs. Therefore, this study recommends that MSMEs focus on improving digital literacy, using analytical tools, and utilizing customer data to increase competitiveness in the global market. This approach will strengthen MSMEs ability to face competitive challenges in the digital era.